2022
DOI: 10.3390/ijms23073510
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells from Healthy and Inflamed Human Gingiva Respond Differently to Porphyromonas gingivalis

Abstract: Gingiva-Derived Mesenchymal Stromal Cells (GMSCs) have been shown to play an important role in periodontitis. However, how P. gingivalis, one of the key etiological agents of the disease, affects healthy (H)- and periodontitis (P)-GMSCs is unknown. To address this problem, we established 10 H-GMSC and 12 P-GMSC lines. No significant differences in morphology, differentiation into chondroblasts and adipocytes, expression of characteristic MSCS markers, including pericyte antigens NG2 and PDGFR, were observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
(94 reference statements)
3
7
0
Order By: Relevance
“…Cumulatively, our results showed that these GMSC lines are very similar to the lines that we had previously established [15] and, as such, were used for the curren experiments.…”
Section: Cytotoxicity and Anti-proliferative Activity Of Gmsc Linessupporting
confidence: 75%
See 3 more Smart Citations
“…Cumulatively, our results showed that these GMSC lines are very similar to the lines that we had previously established [15] and, as such, were used for the curren experiments.…”
Section: Cytotoxicity and Anti-proliferative Activity Of Gmsc Linessupporting
confidence: 75%
“…The staining of tissue sections with anti-CD146 mAb and anti-CD31 mAb (an endothelial marker) identified CD146 + CD31pericytes (Figure 1b). Cumulatively, our results showed that these GMSC lines are very similar to the lines that we had previously established [15] and, as such, were used for the current experiments.…”
Section: H-gmscs P-gmscssupporting
confidence: 74%
See 2 more Smart Citations
“…TGF-β1 is also involved in angiogenesis and serves as a pivotal immunosuppressive secreted polypeptide. Moreover, as a versatile growth factor, it governs various behaviors and functions of fibroblasts and MSCs, thereby orchestrating tissue remodeling by producing connective tissue constituent and matrix proteins [56]. In our study, both VEGF-A and TGF-β1 mRNA levels increased when cultured on GPP within a two-week period, whereas VSCM only showed significant effects after 7 days.…”
Section: Discussionmentioning
confidence: 48%